PENGARUH EXPERIENTIAL MARKETING TERHADAP MINAT KUNJUNG ULANG WISATAWAN KAWASAN OBJEK WISATA LEMBAH HARAU KABUPATEN LIMA PULUH KOTA - Nuzulia Mustika Dhani; Firman Firman (Jurnal Praktik Bisnis, 2015)
This study aimed to analyze the effect of sense, feel, think and act toward revisit interest of tourist for Lembah Harau tourism in Kabupaten Limapuluh Kota. This research included type of caustive research. Populations on this study are all tourist who visited of Lembah Harau. By using the formula slovin, then selected a sample size of 100 people, which is carried out by sampling Accidental. The data analysis technique used is the analysis of the multiple regression using SPSS version 16.00. The results based multiple regression analysis showed that: sense, feel, think and act variabel has a significant effect toward revisit interest for Lembah Harau tourism. Keywords: Sense, Feel, Think, Act, Revisit Interest, Lembah Harau Tourism.